Investigation of hydrodynamic and heat transfer characteristics of gas–liquid Taylor flow in vertical capillaries. (May 2016) - Zhang, Jingzhi; Li, Wei
Abstract: Heat transfer and flow characteristics of Taylor flow in vertical capillaries with diameters of 0.5, 1, and 2 mm have been investigated numerically with the volume of fluid method. 30 different cases have been conducted with inlet Reynolds number ranging from 100 to 500 and initial void fraction ranging from 0.2 to 0.4. Simulation results of the normalized bubble rising velocity, frictional pressure drops, and average Nusselt number fit well with the experimental data and empirical correlations. The results indicate that the normalized bubble rising velocity is related to the capillary number. The flow-pattern dependent and modified Lockhart–Martinelli correlations can predict the numerical frictional pressure drops well. A low temperature region is formed in the liquid slug, where a recirculation zone is formed. The average Nusselt number increases with increasing Re, tube diameters, and with decreasing ξ G, and is about 1.2 ~ 3 times of that of a fully developed laminar single phase flow in circular tubes with constant wall heat flux boundary conditions.